Mutational analysis of the tuberous sclerosis geneTSC2 in patients with pulmonary lymphangioleiomyomatosis. Issue 1 (1st January 2000) - Astrinidis, Aristotelis; Khare, Leena; Carsillo, Thomas; Smolarek, Teresa; Au, Kit-Sing; Northrup, Hope; Henske, Elizabeth Petri
Abstract : Pulmonary lymphangioleiomyomatosis (LAM) is a rare disorder limited almost exclusively to women of reproductive age. LAM affects about 5% of women with tuberous sclerosis complex (TSC). LAM also occurs in women who do not have TSC (sporadic LAM). TSC is a tumour suppressor gene syndrome characterised by seizures, mental retardation, and tumours in the brain, heart, and kidney. Angiomyolipomas, which are benign tumours with smooth muscle, fat, and dysplastic vascular components, are the most common renal tumour in TSC. Renal angiomyolipomas also occur in 63% of sporadic LAM patients. We recently found that 54% of these angiomyolipomas have TSC2 loss of heterozygosity, leading to the hypothesis that sporadic LAM is genetically related to TSC. In this study, we screened DNA from 21 women with sporadic LAM for mutations in all 41 exons of TSC2 . Twelve of the patients had known renal angiomyolipomas. No TSC2 mutations were detected. We did find three silent TSC2 polymorphisms. We conclude that patients with sporadic LAM, including those with renal angiomyolipomas, do not have a high frequency of germline mutations in the coding region of TSC2 .